Why AI is the Future of Healthcare: An Evidence-Based Analysis - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Why AI is the Future of Healthcare: An Evidence-Based Analysis The integration of Artificial Intelligence (AI) into healthcare is no longer a theoretica...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation